Business Plan & Marketing Plan: Fondasi Utama Kesuksesan - Erni Dina Zuliyanti; Haniatul Kiromah; Muhamad A’tho Fiizatillah; Fandi Kurniawan; Ferida Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Business Plan & Marketing Plan: Fondasi Utama Kesuksesan Business planning and marketing strategy play an important role in maintaining business sustainability amid increasingly competitive market conditions. This article discusses the meaning of a business plan, the scope of marketing activities, and the role of marketing plans in market expansion. A business plan serves as a guideline for managing a business, including setting objectives, preparing marketing strategies, organizing operational systems, and managing finances. Meanwhile, marketing planning helps companies understand consumer needs, identify target markets, and develop suitable promotional strategies. In today’s business environment, companies are expected to adapt to changes in consumer behavior, technological development, and shifting market conditions. Appropriate marketing strategies can help businesses build brand image, increase customer trust, and expand market reach. Objectives: To explain the importance of business plans and marketing plans in supporting business development and market expansion. Methods: This article applies a qualitative descriptive approach through a literature study. Results: The discussion shows that business plans and marketing plans help companies understand market conditions, determine marketing strategies, and improve business competitiveness. Conclusion: Business success is influenced not only by product quality, but also by proper planning and effective marketing strategies. Contribution: This article provides an understanding of the importance of business and marketing planning in developing sustainable businesses.